2021
DOI: 10.4103/ijmbs.ijmbs_5_21
|View full text |Cite
|
Sign up to set email alerts
|

Family history in patients with end-stage renal disease on hemodialysis in Tripoli, Libya

Abstract: Background: End-Stage Renal Disease (ESRD) is a global health problem due to increasing its burden worldwide. High-risk groups include family members of patients with ESRD. Objectives: To determine the prevalence of ESRD among dialysis patients' families. At Al-Shat kidney dialysis Center, Tripoli, Libya. So can conclude that the ESRD patient is an index case for a high- risk population. Methods: All patients' data were collected through direct interview with the patients for 15- 20 minutes and by reviewing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…The present study reported that 16% of hemodialysis patients were diabetics which is higher than study conducted in Sana'a (35), Hudaidha cities, Yemen (14). Diabetes mellitus is the leading cause of CRF and accounts for 50% of ESRD causes in both developed and developing countries (26,32). Although, CRF as a complication of medications intake as analgesics represents 29% of sample compared to 5% in Tabuk, Saudi Arabia (20( but the result of this study revealed that there was no correlation between NSAID using and gender of CRF patients which is identical to studies conducted in Saudi Arabia and Yemen (4,20,39).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The present study reported that 16% of hemodialysis patients were diabetics which is higher than study conducted in Sana'a (35), Hudaidha cities, Yemen (14). Diabetes mellitus is the leading cause of CRF and accounts for 50% of ESRD causes in both developed and developing countries (26,32). Although, CRF as a complication of medications intake as analgesics represents 29% of sample compared to 5% in Tabuk, Saudi Arabia (20( but the result of this study revealed that there was no correlation between NSAID using and gender of CRF patients which is identical to studies conducted in Saudi Arabia and Yemen (4,20,39).…”
Section: Discussionsupporting
confidence: 70%
“…The WHO contends that chronic Khat-chewing can cause hypertension in young adults, with a spontaneous regression once consumption is stopped (30). From this study, nearly more than half of patients were smokers, however 49% were nonsmokers, previous studies revealed that there was no significant relationship between smoking and the incidence of CRF (32,33,22). Whereas other studies reported that there is a correlation between smoking and the incidence of CRF (21,34).…”
Section: Discussionmentioning
confidence: 45%